Timing of congenital cytomegalovirus diagnosis and missed opportunities - Baker, Mallory R.; Wang, Xing; Melvin, Ann J. (Frontiers in Pediatrics, 2025)
ObjectiveAlthough congenital cytomegalovirus (cCMV) is the most common congenital infection world-wide, many infected infants are not diagnosed at birth. Anticipating that infants with cCMV who are not tested at birth risk a delayed diagnosis, this study was conducted to investigate the timing of diagnosis for infants with cCMV and to determine the reasons for and impact of late diagnoses.MethodsClinical, imaging and laboratory data, hearing and developmental outcomes were abstracted from medical records between 2009 and 2021 for infants with virologically confirmed cCMV.ResultsOne hundred and twelve children with confirmed cCMV were identified. Diagnosis was within the first three weeks of life for 60 (54%) (early diagnosis group/EDG) and after this time for 52 (46%) (late diagnosis group/LDG). Infants in the LDG were diagnosed via CMV PCR on neonatal dried blood spot specimens with the majority (71%) tested after identification of sensorineural hearing loss (SNHL). The median time to first CMV testing in the LDG was 12 (IQR 3–42) months. Symptoms consistent with cCMV were present at birth in 17 (33%) of the infants with delayed diagnosis. More infants in the EDG received antiviral treatment (n = 41, 68% vs. n = 19, 23%). Developmental outcomes were similar between groups. Applying different screening strategies to the total cohort, 100%, 66% and 92% could have been diagnosed at birth with universal, hearing targeted and expanded testing strategies respectively.ConclusionThe lack of formal protocols for cCMV testing leads to delayed diagnoses for many infants. This delay results in missed opportunities for monitoring, intervention, and treatment.